Effect of electrophysiological mapping on non-transmural annulus ablation and atrial fibrillation recurrence prediction after 6 months of Cox-Maze IV procedure - Sun, Zhishan; Fan, Chengming; Song, Long; Zhang, Hao; Jiang, Zenan; Tan, Haoyu; Sun, Yaqin; Liu, Liming (Frontiers in Cardiovascular Medicine, 2022)
Objective The objective of this study was to observe the safety and efficacy of electrophysiological mapping following the Cox-Maze IV procedure and to investigate whether a correlation exists between recurrence of atrial fibrillation (AF) with the completeness of bidirectional electrical isolation and the inducibility of AF immediately after the Cox-Maze IV procedure. Methods Totally, 80 consecutive patients who suffered from aortic valve or mitral valve disease and persistent AF were randomly enrolled into the control group and electrophysiological mapping following the Cox-Maze IV group (Electrophysio-Maze group). In the Electrophysio-Maze group, patients underwent concomitant Cox-Maze procedure and following electrophysiological mapping of ablation lines in mitral isthmus, left atrial “box,” and tricuspid annulus. If the bidirectional electrical isolation of tricuspid annulus ablation line is incomplete, whether to implement supplementary ablation will be independently decided by the operator. Before and after the Cox-Maze IV procedure, AF induction was performed. All patients in both groups were continuously followed-up and underwent electrocardiogram Holter monitoring after 6 months. Results In total, 42 Electrophysio-Maze patients and 38 controls were enrolled. Compared with patients in the control group, there were shorter hospital stay, better cardiac remodeling changes, and higher relief from AF during the follow-up period of 6 months in the Electrophysio-Maze group. Within the Electrophysio-Maze group, the rate of incomplete the bidirectional electrical isolation of “box” ablation lines was zero, and the rate of incomplete bidirectional electrical isolation of mitral isthmus ablation line or tricuspid annulus ablation line was 23.8%. After two cases of successful complementary ablation on the tricuspid annulus ablation line, the final incomplete bidirectional electrical isolation of annulus ablation lines was 19.0%. There were correlations between late AF recurrence after 6 months with incomplete bidirectional electrical isolation of annulus ablation lines and AF induction immediately after the Cox-Maze IV procedure. Conclusion Electrophysiological mapping following the Cox-Maze procedure is safe and effective. Electrophysiological mapping in the Cox-Maze procedure can find out the non-transmural annulus ablation lines by assessing the completeness of bidirectional electrical isolation of ablation lines, guide supplementary ablation, and predict AF recurrence after 6 months.